Biogenic Synthesis of Zinc Oxide Nanoparticles with Leaves and Cones Concentrate of Cupressus Arizonica and Assessment of Photocatalytic and Antibacterial Efficiency - Ustun Ozgur, Mahmure; Ortadogulu, Ebru; Erdemir, Burak; Aydin Kurc, Mine (GAZI UNIV, 2024)
Among the metal oxide nanoparticles, zinc oxide (ZnO) has recently been cited as the new material of the future due to its unique properties and wide application areas. In this study, we offer a simple technique for the production of extremely stable ZnO nanoparticles (CA-ZnO NPs) using the aqueous and ethyl alcohol (1/1, v/v) extract of Cupressus arizonica (CA, Blue cypress) leaves and cones and zinc acetate (Zn-Ac) salt. The structure of the produced CA-ZnO NPs was elucidated and nanoparticles were used as a photocatalyst for the removal of textile dyestuffs. The particle sizes of CA-ZnO NPs calcined at different temperatures (60 degrees C, 150 degrees C, and 400 degrees C) increased from 20 nm to 50 nm. Produced CA-ZnO NPs were used to investigate photocatalytic Blue (BB3) and Basic Red 46 (BR46) in aqueous solution under UV- light and daylight irradiation. After stirring dye solutions containing CA-ZnO NP for one hour in darkness and 7 hours under UV- light, decolorization rates varied from 53% to 100%. Decolorization of the dyestuff molecules follows the pseudo first-order kinetics. Produced CA-ZnO NPs showed antibacterial efficiency against Escherichia coli and Staphylococcus aureus. CA-ZnO NPs formed zones ranging from 10 mm to 11 mm against gram+ and gram- bacteria. Green production of ZnO NPs utilizing Cupressus arizonica plant extract can replace chemical methods, and the resulting CA-ZnO NPs can be used in industries like water purification. This eco-friendly biogenic synthesis method is a new, inexpensive and useful technique suitable for large scale.
Keywords: Zinc oxide; Cupressus arizonica; Photocatalyst; Antibacterial; Textile dye; ZNO NANOPARTICLES; GREEN SYNTHESIS; LEAF EXTRACT; ANTIMICROBIAL ACTIVITY; DEGRADATION; FLOWER; Science & Technology - Other Topics